Distributed Sensor Networks Image and Sensor Signal Processing - Iyengar, S. S. and Brooks, R. R. (Boca Raton : CRC Press, 2012)
The six years since the first edition appeared has seen the field of sensor networks ripen. The number of researchers working in the field and the number of technical (journal and conference) publications related to sensor networks have exploded. Those of us working in the field since its infancy have been gratified by the large number of practical sensor network applications that are being used. Not surprisingly, a number of lessons have been learned. The current state of affairs could hardly have been predicted when the first edition went to press. Partly because of this, we were extremely gratified when Chapman & Hall contacted us and suggested printing a revised second edition of Distributed Sensor Networks--
v. 1. Image and sensor signal processing -- v. 2. Sensor networking and applications.
vol. 1
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Sensor networks; Multisensor data fusion; Intelligent agents (Computer software); Electronic books